Adrenal aldosterone synthase (CYP11B2) histopathology and its association with disease-induced sudden death: a cross-sectional studyResearch in context - Antero Ylänen; Juhani Isojärvi; Antti Virtanen; Helena Leijon; Tiina Vesterinen; Aapo L. Aro; Heini Huhtala; Eeva Kokko; Ilkka Pörsti; Marianna Viukari; Pasi I. Nevalainen; Niina Matikainen (The Lancet Regional Health. Europe)
Summary: Background: Unidentified cardiovascular risk factors may account for approximately half of sudden deaths, a devastating event with limited preventive tools. We investigated whether adrenal histopathology suggestive of primary aldosteronism, pheochromocytoma, or adrenal masses could explain part of the risk for disease-induced sudden death (DSD). Methods: In this study, autopsies and histopathological analyses, including aldosterone synthase staining of adrenal glands, were performed on 403 consecutive individuals who experienced sudden death. These individuals were classified into 258 cases of DSD and 144 deaths caused by trauma, suicide, or intoxication, i.e., non-disease-induced sudden death (nDSD). This trial was registered at ClinicalTrials.gov (NCT05446779). Findings: Adrenal histopathology revealed changes in 31 (7.7%) subjects of the cohort. Of these, the most prevalent findings [25 (6.2%)] were aldosterone-producing adenomas (APA) or nodules (APN), which were associated with myocardial infarction and atherosclerosis at autopsy. Individuals in the DSD group and the subgroup with sudden cardiac death (SCD) were more likely to have APA or APN than individuals in the nDSD group [23 (8.9%) vs. 2 (1.4%), p = 0.002; 16 (8.8%) vs. 2 (1.4%), p = 0.003, respectively]. APA or APN were explanatory factors for DSD (odds ratio [OR] 6.47, 95% confidence interval [CI] 1.40–29.88, p = 0.017) and SCD (OR 10.68, 95% CI 2.02–56.43, p = 0.005). Other findings included two pheochromocytomas, one bilateral adrenal metastasis, and two unilateral adrenal metastases. Interpretation: In this exploratory study, APA or APN were more frequently seen in DSD and SCD than nDSD cases. Whether primary aldosteronism constitutes a novel risk factor for sudden death warrants further study. Funding: Finnish State Research funds and independent research foundations: Aarne Koskelo Foundation, the Finnish Kidney Foundation, and the Finnish Foundation for Cardiovascular Research.